A SWOT matrix of PSMB system integration / Nur Anis Afifah Mohamad - Mohamad, Nur Anis Afifah (2010)
This research report presents the study on the research which is about a SWOT matrix of Pusat Sistem Maklumat Bersepadu (PSMB) system integration. The main goal of this research is to analyze the strengths, weaknesses, opportunities and threats in system integration at PSMB by using a Strengths, Weaknesses, Opportunities, Threats (SWOT) matrix. It is important to use a suitable tool in order to analyze the problems, advantages and issues in system integration. The scope of the research only focused at Pusat Sistem Maklumat Bersepadu (PSMB) which is located in University Technology MARA (UITM). In order to complete this research, the research methodology needs to be well conducted. The methodology consists of four phases which are research planning, knowledge acquisition, data analysis and final documentation. The data that obtained from interviewing and literature review will be analyzed in order to get information and achieve the two main objectives. At the end of this research, better understanding is achieved about the problems, advantages and other issues related to PSMB system integration.